Progress of Immunotherapy and Its Application in Triple Negative Breast Cancer - ZHENG Hongmei; FENG Yaojun; XU Juan; CHENG Hongtao; JIN Liting; ZHONG Wei; WU Xinhong (Zhongliu Fangzhi Yanjiu, 2020)
In recent years, potential new therapeutic options have been yielded for the immunotherapy of invasive cancers. The most important breakthrough in breast cancer research today is to understand the immune features and profiles of triple negative breast cancer and then design novel immune-modulatory targeted therapy. The major findings are the use of immune checkpoint inhibitors, which have obtained good curative effect in neoadjuvant treatment for early stage triple negative breast cancer and salvage treatment for metastatic triple negative breast cancer. This paper summarizes the advances of immunotherapy and its application in triple negative breast cancer with emphasis on immune checkpoint inhibitor and its combination with chemotherapy, radiotherapy and targeted therapy.